The Lecture Method of Teaching Literature in the Middle of the XIX – Early XX Century - Novakivska, Liudmyla (Pedagogical Discourse, 2016)
The article analyzes the practice of lecture method in class literature in the middle of the XIX – early XX century. It is noted that the tradition of teaching literature in the analyzed period was based on a combination of heuristic (conversation method) and dogmatic (lecture) teaching methods. Methodists in many ways determined the value of the lecture in the teaching of literature in high school, emphasized the uniqueness of the lecture on the lessons of literature, suggesting psychological, didactic and methodological features of the application of the lecture method in the school of historical and literary courses. It was found that regular use of lectures in the study of literary history course in high school. At the same time, the specificity of the school lecture was a combination of elements in it as academic lectures, adopted in high school, as well as elements of literary conversation, as a method of an average level of education. Key words: lecture method, literature, literature, teaching literature in the middle of the XIX – early XX century.